Learning statistics: Experiences of senior citizen students in the Social Sciences at Universiti Sains Malaysia, Penang, Malaysia. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2011)
Learning statistics is difficult for many students especially those with little or no prior statistical or mathematical training (Onwuegbuzie & Wilson, 2003).